Human Factors in Pharmacy. (September 2017) - Chui, Michelle A.; Holden, Richard J.; Russ, Alissa L.; Abraham, Olufunmilola; Srinivas, Preethi; Stone, Jamie A.; Jahn, Michelle A.; Ozkaynak, Mustafa
Medication errors in the ambulatory setting are common and contribute to significant morbidity and mortality. Given the Institute of Medicine's recommendation of adopting a systems-based approach to improving medication safety, research has been conducted utilizing human factors and ergonomics conceptual frameworks, approaches, and methods to study pharmacies and pharmacists. This panel will focus on how human factors principles and models have been adapted for contexts where medications are managed. Individual projects address pediatric patients' medication-related needs, over-the-counter medication safety for older adults, anticoagulation management, automated prescription tracking, and medication safety-related decision making by healthcare professionals. These studies span settings from community pharmacies to inpatient pharmacies to specialty clinics and patients' homes. By presenting a sample of the growing body of human factors work in pharmacy, this panel will offer unique implications for human factors theory, methods, and application in this important domain.